Characteristics of Moyamoya Syndrome in Sickle-Cell Disease by Magnetic Resonance Angiography: An Adult-Cohort Study - Kauv, Paul; Gaudré, Noémie; Hodel, Jérôme; Tuilier, Titien; Habibi, Anoosha; Oppenheim, Catherine; Edjlali, Myriam; Hervé, Dominique; Calvet, David; Bartolucci, Pablo (Frontiers in Neurology, 2019)
Background: Sickle cell disease (SCD) can be complicated by moyamoya syndrome. Brain magnetic resonance angiography (MRA) is a noninvasive method to diagnose this syndrome and, steno-occlusion and moyamoya vessels (MMV) scores have been proposed to evaluate its severity. The objective was to assess the characteristics of moyamoya syndrome in an adult cohort of SCD using these MRA scores. Methods: 25 SCD patients with moyamoya syndrome were included using MRA with 3D time of flight technique. We evaluate steno-occlusion score for each hemisphere (range 0–10) from: steno-occlusion severity of internal carotid (ICA) (0-3), anterior cerebral (ACA) (0-3), middle cerebral (MCA) (0-2) and posterior cerebral (PCA) (0-2) arteries. MMV score for each hemisphere (range 0-5) depended from 5 MMV areas: 1. anterior communicating artery 2. basal ganglia 3. ICA/MCA 4. posterior communicating artery/PCA 5. basilar artery. Results: 8 patients (32%) showed unilateral moyamoya syndrome. ICA steno-occlusion was involved in 22 patients (88%), MCA in 23 patients (92%), ACA in 9 patients (36%) and PCA in 3 patients (12%). MMV involved ACoA area in 10 patients (40%), basal ganglia in 13 patients (52%), PCoA/PCA in 10 patients (40%), MCA/ICA in 7 patients (28%) and BA in 1 patient (4%). Steno-occlusion and MMV mean hemisphere scores were 3.4/10 (± 1.42) and 1.6/5 (± 0.71), respectively. Conclusion: Frequent unilateral moyamoya syndrome, uncommon PCA involvement and, moderate steno-occlusion and MMV scores seem to be features of SCD moyamoya syndrome. In future studies, MRA scores could be collected to assess the follow-up in these patients.